Exploring the brand image of an Islamic higher educational institution: a qualitative approach - Haque, A. K. M. Ahasanul (medi+WORLD Internationa, 2014)
Abstract The purpose of the study is to explore the brand image of an Islamic higher educational institute among the current students. A qualitative (phenom-enology) approach is applied, using the interview method. A total of 7 students were selected purposefully as the respondents from different dis-ciplines, study levels and gender. To apply the rigorous qualitative analysis, it follows several procedures like audio recording, immediate transcripts and the cross checks of the write up. The study found the students aware about the brand image of the concerned university. The study reveals that “International Islamic University Malaysia (IIUM)” as a higher educational institute has a positive brand image among the current students though the level of positivity varies from case to case. Respondents’ brand feeling about “IIUM” is constructive as a higher education provider. A more com-prehensive research can be done including a greater number of respond-ents as the study includes only seven. The study shows the preliminary way to explore the existing students thoughts about the image of a higher educational institution. It may assist the university’s top management or marketing division to explore the brand image of their institute and take on brand building programs accordingly. The study is exclusive to explore the students’ thoughts about the brand image of a higher educational institute.